Inovasi Teknologi Internet of Things pada Budidaya Tanaman Hidroponik di Desa Jambewangi – Banyuwangi - Alfian Pradiknatama; Agus Supriono; Cindera Rosa Damascena; Rizky Yanuarti; Indah Ibanah; Rena Yunita Rahman; Ariq Dewi Maharani (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2025)
The Covid19 pandemic had a major impact on the weakening of Indonesia's economic sector, including Small, Micro and Medium Enterprises (MSMEs). The MSME sector is one of the sectors that makes a major contribution to the national economy so it needs to rise during the current Covid19 pandemic. Jambewangi Village is a village located in Sempu District, Banyuwangi Regency, East Java Province. The area of Jambewangi Village is 1,422 Ha / m2 divided into six hamlets including Krajan Hamlet, Panjen Hamlet, Parastembok Hamlet, Sumberjo Hamlet, Tlogosari Hamlet, and Sidomulyo Hamlet. In Jambewangi Village, it has an interesting landscape, such as a homogeneous forest in the form of pines, the confluence of tributaries with branches, a large expanse of rice fields, as well as fields and plantations. The area of Jambewangi Village is at an altitude of 340-800 masl so it has cool air and is good for growing various kinds of fruits and vegetables.